Induction of desiccation tolerance in desiccation sensitive Citrus limon seeds. Issue 5 (28th March 2019) - Marques, Alexandre; Nijveen, Harm; Somi, Charles; Ligterink, Wilco; Hilhorst, Henk
Abstract: Many economically important perennial species bear recalcitrant seeds, including tea, coffee, cocoa, mango, citrus, rubber, oil palm and coconut. Orthodox seeds can be dried almost completely without losing viability, but so‐called recalcitrant seeds have a very limited storage life and die upon drying below a higher critical moisture content than orthodox seeds. As a result, the development of long‐term storage methods for recalcitrant seeds is compromised. Lowering this critical moisture content would be very valuable since dry seed storage is the safest, most convenient and cheapest method for conserving plant genetic resources. Therefore, we have attempted to induce desiccation tolerance (DT) in the desiccation sensitive seeds of Citrus limon . We show that DT can be induced by paclobutrazol (an inhibitor of gibberellin biosynthesis) and we studied its associated transcriptome to delineate the molecular mechanisms underlying this induction of DT. Paclobutrazol not only interfered with gibberellin related gene expression but also caused extensive changes in expression of genes involved in the biosynthesis and signaling of other hormones. Paclobutrazol induced a transcriptomic switch encompassing suppression of biotic‐ and induction of abiotic responses. We hypothesize that this is the main driver of the induction of DT by paclobutrazol in C. limon seeds. Abstract : Most seeds can be completely dried without losing viability. However, some seeds do not survive drying, including the seeds from citrus. Inventing ways to make desiccation sensitive seeds tolerant would benefit their long‐term conservation. We report the manipulation of hormone levels can induce the desiccation tolerance in citrus seeds.